PERCEPCION DE SEGURIDAD DE LA INFORMACION EN LAS PEQUENAS Y MEDIANAS EMPRESAS EN SANTO DOMINGO - Guaman, Carlos Roberto Sampedro; Vivar, Silvio Amable Machuca; Rivera, Diego Paul Palma; Calderon, Frankz Alberto Carrera (Investigación operacional, 2019)
The applications of a computer and the way to program them have evolved in a very fast way in the world and consequently in Ecuador, advances that impact in the educational field. The teaching of algorithms is a basic subject of engineering careers in Systems and Software, requires students to develop logical reasoning, so that the initial dropout in this area is high. Students think that programming a computer is a trial-and-error process in a programming language. To avoid this, we must have specific elements and an appropriate methodology that motivate the students to visualize in a concrete way the results of the programs written by them. A diagnosis is presented on the development of the programming logic of the students of the systems and software careers of the face-to-face and blended modalities of the extension of the Autonomous Regional University of the Andes (UNIANDES) in Santo Domingo, the learning habits of the students, teaching methods and techniques of the teacher. To this end, a survey was applied to all students of Systems and Software careers, teachers were interviewed, a pilot survey of students from the Catholic University in Santo Domingo and participatory observation. Obtaining results that demonstrate the need to improve the teaching-learning strategy of algorithms to achieve a better development of programming logic, as a basis for a student of systems engineering and software. KEYWORDS: Teaching programming, programming logic, programming language. Systems engineering, algorithms. Todas las Empresas e Instituciones publicas y privadas tienen un gran volumen de informacion confidencial sobre su estado financiero, productos, proveedores, clientes, y otros datos. Con el uso de sistema informatico, esta informacion es reunida, tratada, almacenada y puesta a disposicion de las personas que deseen revisarla de forma local o remota. De darse el caso de que la informacion caiga en manos no autorizadas, se pierda por danos en el computador o se contamine por malware, supone graves consecuencias, ya que la empresa perdera credibilidad de los clientes, perdera posibles negocios, se puede enfrentar a demandas e incluso puede causar la quiebra de la empresa. Ante este problema la respuesta es la Seguridad Informatica, este campo ofrece muchas areas de especializacion una de ellas la seguridad de la informacion, que implica una inversion cuyos valores no son considerados en el presupuesto de las Pequeias y Medianas Empresas (PyMES) en Santo Domingo de los Tsachilas, ya sea por desconocimiento o por los altos costos, deciden entonces correr el riesgo con las consecuencias ya mencionadas. Fue necesario generar datos estadisticos en materia de seguridad de la informacion para que los empresarios hagan conciencia de los problemas a los que estan expuestos y las medidas que deben implementar en medidas proactivas y reactivas para proteger uno de los activos mas valiosos con los que cuenta las PyMES, la informacion tanto fisica como digital. PALABRAS CLAVE: Seguridad, PyMES, Informacion, Seguridad de la Informacion, Seguridad informatica.